2017
DOI: 10.1016/j.rmed.2017.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer screening and the effects of competing causes of death in the ACRIN-NLST sub-study

Abstract: Background: Suicide in depressed patients is a major health concern and has gained substantial attention in public health fields. However, the role of COPD, with or without lung cancer, in suicide attempts in patients with depression remains unknown. This study aimed to assess whether COPD and lung cancer precipitates suicide attempts. Methods: We identified 1397 depressed adolescents and adults with comorbid COPD alone or alongside lung cancer. Depression types were postpartum depression (n¼145), pre-menstrua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Substantial comorbidities may impact the benefit from screening, particularly in those who are at increased risk of death from competing respiratory and cardiovascular causes, and who may be at higher risk of complications from diagnostic procedures and may be unable to undergo curative treatment. 21 Studies reporting on the impact of PHC on lung cancer outcomes have yielded conflicting results. An early study of 2991 patients with resected stage I NSCLC revealed that in 192 patients with PHC, lung cancer survival was worse (hazard ratio ¼ 1.44, 95% CI: 1.16-1.78).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial comorbidities may impact the benefit from screening, particularly in those who are at increased risk of death from competing respiratory and cardiovascular causes, and who may be at higher risk of complications from diagnostic procedures and may be unable to undergo curative treatment. 21 Studies reporting on the impact of PHC on lung cancer outcomes have yielded conflicting results. An early study of 2991 patients with resected stage I NSCLC revealed that in 192 patients with PHC, lung cancer survival was worse (hazard ratio ¼ 1.44, 95% CI: 1.16-1.78).…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52][53] Screening individuals with advanced COPD remains controversial as they may not benefit from screening due to inoperability and an increased risk of respiratory and other competing causes of death. 54,55 The utilisation of functional assessment tools, such as the BODE index, 56 is suggested to be a better way of assessing the severity and fitness of patients with advanced COPD by incorporating not only the degree of airflow obstruction but also functional dyspnea, bodymass index, and exercise capacity. 15,56 We also estimated the prevalence of four lung diseases: chronic bronchitis, asthma, bronchiectasis, and pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to determine the threshold where the benefits of reducing lung cancer death outweigh the risk of dying from a competing cause, and this can serve to improve survival. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%